Benevolent technotopias and hitherto unimaginable meats: Tracing the promises of in vitro meat. (October 2016) - Jönsson, Erik
Today, in vitro (Latin: in glass ) meat researchers strive to overhaul meat production technologies by producing meat outside animal bodies, primarily by culturing cells. In the process, meat should become healthier, more environmentally friendly and kinder to animals. In this article, I scrutinize (and problematize) this promissory discourse by examining the world that proponents envision alongside the world from which promises emerge. First, I trace the increasing number of publications striving to pinpoint the nature of in vitro meat to unveil the creation of an in vitro meat canon wherein perceived possibilities become taken for granted. Second, I investigate how the promissory discourse is often relatively silent on key aspects of how this technology could remake the world. Wet laboratories, animals and end products become foregrounded at the expense of political economy and the biophysical properties of cultured cells. Thus, questions concerning how funding requirements shape representations of this new technology, together with in vitro meat's particular socio-spatial and socio-ecological implications, become problematically de-emphasized.